Teaching Processes and Technology Use in the Classroom [Procesos Pedagógicos y Uso de Tecnología en el Aula] - Villalta-Paucar, M (Universidad Complutense de Madrid, 2015)
Computer supports have diversified the possibilities for interactivity in classroom teaching. Collaborative games, response feedback systems and simulated participation are indicative of the wide range of activities for which these technologies have found application in classroom education processes. In this article, evidence is offered for the contributions made to classroom pedagogical processes by computer mediation. The bibliographic analysis conducted permitted the identification of 2 pedagogic processes generated, an inductive and a deductive one, were identified. The computer-mediated teaching activities associated with each process in this literature were then classified and analyzed. Finally, inferences were drawn regarding the advantages of computer mediation in this scenario, being the main contributions, structuring and gradual deepening of subject content, the strengthening of collaboration processes, the diversification of learning environments and increased student participation. © 2015 Universidad Complutense de Madrid. All rights reserved.